Sosialisasi KRS BP2P untuk Peningkatan Kualitas Permukiman Pariwisata di Desa Aik Bukaq - Prasetiawan, Jauhari; Patoni , Khairul; Fadhiyani, Zidya; Hendrianto, Hendrianto; Habiburrahman, Habiburrahman (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
The SPA RPMA (Strategic Planning Area - Regional Planning and Management Agency) socialization aims to enhance the quality of tourism settlements in Aik Bukaq Village. This village has untapped tourism potential, and improving infrastructure and area management is crucial to attract more tourists. Aik Bukaq Village, with its rich natural beauty and culture, has significant potential as a tourist destination. However, inadequate settlement infrastructure and unintegrated area management affect the quality of the tourist experience and the well-being of local residents. RPMA intends to implement strategic improvements through SPA socialization to address these conditions. The results of this socialization show an increased awareness and understanding among the community regarding the importance of infrastructure improvements and area management. Overall, SPA RPMA socialization has successfully laid the foundation for enhancing the quality of tourism settlements in Aik Bukaq Village, which is expected to drive local economic growth and attract more tourists to the village.